2013
DOI: 10.1177/1941874412470665
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Falls

Abstract: In this 2 part series, analysis of the risk stratification tools that are available, definition for the scope of the problem, and potential solutions through a review of the literature are presented. A systematic review was used to identify articles for risk stratification and interventions. Three risk stratification systems are discussed, St Thomas's Risk Assessment Tool in Falling Elderly Inpatients, Morse Fall Scale, and the Hendrich Fall Risk Model. Of these scoring systems, the Hendrich Fall Risk Model is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 72 publications
1
17
0
1
Order By: Relevance
“…A full table of contents appears in online Appendix 1. Additionally, portions of the curriculum have been published online 21, 22. Topic selection was guided by the Accreditation Council for Graduate Medical Education (ACGME) core geriatrics topics determined most relevant for the inpatient setting.…”
Section: Methodsmentioning
confidence: 99%
“…A full table of contents appears in online Appendix 1. Additionally, portions of the curriculum have been published online 21, 22. Topic selection was guided by the Accreditation Council for Graduate Medical Education (ACGME) core geriatrics topics determined most relevant for the inpatient setting.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the patients who were judged as being at high risk by the STRATIFY score did not fall, and intervention for the high-risk patients often ended up being wasted. Therefore, cost-effectiveness analysis is necessary to use the STRATIFY score as a tool for target intervention for patients who have been assessed as being at high risk for falls (Cumbler, Simpson, Rosenthal, & Likosky, 2013 and meta-analysis of the STRATIFY score and suggested that the STRATIFY score should not be used in isolation (Billington, Fahey, & Galvin, 2012). Rather, they suggested that the tool could be used in step 1 of a fall management strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Rumah sakit mengembangkan dan meneraplan proses untuk mengurangi risiko cedera akibat pasien jatuh sebagai upaya mencegah terjadinya insiden ini (JCI, 2014). Tenaga kesehatan perlu mempertimbangkan faktor penyebab ganggungan keseimbangan atau faktor lain sebagai penyebab pasien cedera akibat pasien jatuh dan diidentifikasi sebagai faktor risiko pengobatan (Barker, Kamar, Graco, Lawlor, & Hill, 2011;Chan, Wadsley, & Ferriere, 2017;Cumbler, Simpson, Rosenthal, & Likosky, 2013;Hoffmann, Neumann, Golgert, & von Renteln-Kruse, 2015;Hung et al, 2017;Latt, Loh, Ge, & Hepworth, 2016;Milisen et al, 2007;Oliver, Britton, Seed, Martin, & Hopper, 1997).…”
Section: Gambar 6 Jumlah Dan Variasi Insiden Terkait Skp6unclassified